2015
DOI: 10.1007/s00705-015-2649-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection with cytopathic bovine viral diarrhea virus in mice induces megakaryopoiesis in the spleen and bone marrow

Abstract: Here, we infected mice with cytopathic bovine viral diarrhea virus 1 (cp BVDV1) by oral inoculation and investigated the effects of infection by histopathological, immunohistochemical (IHC), hematological methods. Twelve mice were infected, and samples were obtained at day 2, 5, and 9 postinfection (pi). Most of the infected mice exhibited clinical signs of illness such as reduced movement, crouching, loose feces, loss of appetite, and reduced water intake. Blood samples from six mice were positive for BVDV ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
9
1
2
Order By: Relevance
“…En un primer experimento, dos grupos de 8 ratones BALB/c (hembras, 6-8 semanas de vida) fueron inoculados por vía intra-peritoneal (IP) con 0,4 ml de una dosis de 5.10 5 DICT50/ml de dos cepas del VDVB. Esta dosis fue la establecida por Seong y colaboradores en su trabajo de puesta a punto de este modelo [144]- [146]. Cuatro animales se dejaron como control sin infectar, y solamente recibieron 0,4 ml de medio de infección.…”
Section: Resultados Desarrollo Del Modelo Murino De Infección Por El unclassified
See 1 more Smart Citation
“…En un primer experimento, dos grupos de 8 ratones BALB/c (hembras, 6-8 semanas de vida) fueron inoculados por vía intra-peritoneal (IP) con 0,4 ml de una dosis de 5.10 5 DICT50/ml de dos cepas del VDVB. Esta dosis fue la establecida por Seong y colaboradores en su trabajo de puesta a punto de este modelo [144]- [146]. Cuatro animales se dejaron como control sin infectar, y solamente recibieron 0,4 ml de medio de infección.…”
Section: Resultados Desarrollo Del Modelo Murino De Infección Por El unclassified
“…La evaluación de la actividad antiviral de los IFNr in vitro arrojó resultados favorables para continuar con el estudio en modelos animales in vivo. Previo a realizar estudios en bovinos decidimos realizar una primera prueba de concepto en el modelo murino para evaluar la actividad de los IFN-α y λ. Trabajos publicados por Seong y col [144], [145] reportan la utilización de ratones BALB/c como modelo de infección para VDVB. De esta manera establecimos primero si los animales se infectaban con cepas de nuestro interés y caracterizamos el perfil de esa infección.…”
Section: Introducción Y Diseño Experimentalunclassified
“…With the exception of rabbits mentioned under Parameter 3 a range of non‐arteriodactyls, including horses, cats, dogs, guinea pigs, mice and embryonated chicken eggs have previously been reported not to be susceptible to infection with BVDV (Baker et al., ), although recent work has suggested that mice can be infected when inoculated by oral and intra‐nasal challenge (Seong et al., , ).…”
Section: Assessmentmentioning
confidence: 99%
“…to be susceptible to infection with BVDV (Baker et al, 1954), although recent work has suggested that mice can be infected when inoculated by oral and intra-nasal challenge (Seong et al, 2015(Seong et al, , 2016.…”
Section: Rabbit (Oryctolagus Cuniculus)mentioning
confidence: 99%
“…We also developed a method to easily measure infectivity of BVDV by visualizing infected cells using a monoclonal antibody against a non-structural protein (NS3), considered a marker of virus replication (25). Recently, a mouse model of BVDV infection was set-up and tested with several strains showing that mice developed viremia without clinically manifest disease (26,27). In this study, we made use of all these tools, set up the BALB/c infection model for 2-well characterized type-2 ncp BVDV strains (28) and evaluated the efficacy of prophylaxis and treatment with IFN-α and IFN-λ in reducing BVDV infection.…”
Section: Introductionmentioning
confidence: 99%